Argumentação e prova: uma experiência em geometria espacial no ensino médio - Vieira, Wellington Zarur Viana (2007)
This work is inserted in Project AProvaME Argumentation and proof in School Mathematics - it has the objective of to do a map of conceptions about students and adolescent s argumentation and proof in schools at State of São Paulo, how this the preparation, application and valuation of the learning situations. To that we expose one sequence of activities that broach Spatial Geometry Concepts, how parallelism and perpendicularity. This sequence of activities was applied to six students age between 14 and 16 years in a State Public School, with the objective of to contribute to the development these students when they are inserted in a argumentation and proof s context on Mathematics. How assistance in this process, we used the software Cabri-Géomètre, with the hypothesis that this could to give a support to visualization of the object in study. The analysis presents that, though the students hadn t searched a level of intellectual proof. There was an important advance on search proprieties and pertinent elements of the figure to justify their answers. The situations woke-up a visible interest on the students, permitting to discuss some aspects that have to be considered in the elaboration of a Geometry proof, related principally the interference of the spatial elements of figural representation